Probabilistic assessment of damaged survivability of passenger ships in case of grounding or contact. (15th December 2020) - Bulian, Gabriele; Cardinale, Mike; Dafermos, George; Lindroth, Daniel; Ruponen, Pekka; Zaraphonitis, George
Abstract: This paper presents a probabilistic framework for the assessment of ship survivability following bottom grounding and side grounding/contact accidents, with specific attention to passenger ships. The proposed framework provides attained subdivision indices for each type of accident. For harmonization reasons and to leverage on the experience of present designers, the proposed approach is consistent with existing SOLAS probabilistic regulations for damaged ship survivability assessment following a collision. In the presented framework, the probability of flooding a (group of) compartment(s), i.e. the so-called "p-factor" associated to each "damage case", is determined using an automatic, flexible and easily updatable non-zonal approach based on Monte Carlo generation of hull breaches according to the underlying geometrical and probabilistic models of damage. The conditional ship survivability metric is assumed to be provided by the SOLAS "s-factor". Results from three example applications are reported and discussed. The information provided in the paper are at a level of detail allowing the implementation of the proposed approach. The obtained results indicate the potential practical applicability of the proposed approach, and the benefits of considering different types of damage for a safety-oriented design and for a proper assessment of stability-related risk control options. Highlights: Presentation of a non-zonal probabilistic framework for damaged ship survivability. Addressing of bottom grounding and side grounding/contact accidents. Focus on passenger ships. Detailed description of geometrical and probabilistic models for breaches. Reporting of results for three example applications.